Chemo-free maintenance therapy in adult T-cell acute lymphoblastic leukemia: A case report and literature review - Song, Yuanbin; Chen, Shuzhao; Liu, Chenfei; Chen, Lezong; Wang, Weida; Wu, Bingyi; Liang, Yang (Frontiers in Pharmacology, 2023)
Maintenance therapy in adult T-cell acute lymphoblastic leukemia (T-ALL) is the longest phase but with limited option. The classic drugs used in the maintenance phase such as 6-mercaptopurine, methotrexate, corticosteroid and vincristine have potentially serious toxicities. Optimizing therapy in the modern age, chemo-free maintenance therapy regimens for patients with T-ALL may dramatically improve the maintenance therapeutic landscape. We report here the combination of Anti-programmed cell death protein 1 antibody and histone deacetylase inhibitor as chemo-free maintenance treatment in a T-ALL patient with literature review, thus providing a unique perspective in addition to valuable information which may inform novel therapeutic approaches.